Prognostic Significance of the Fission1/Parkin Ratio for Sepsis: A Prospective Cohort Study - Huang, Wei; Wang, Xiaoting; Zhang, Hongmin; Wang, Guangjian; Liu, Dawei (Frontiers in Medicine, 2021)
Introduction: Fission1 (Fis1) and parkin are key proteins related to mitochondrial fission and mitophagy, respectively. This study aimed to assess the prognostic value of the Fis1/parkin ratio as a biomarker in patients with sepsis. Methods: Consecutive patients with sepsis (n = 133) or simple infection (n=24) were enrolled within 24 h of arrival at the intensive care unit (ICU). Serum levels of Fis1, parkin, mitofusin2 (Mfn2), and peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) were measured by enzyme-linked immunosorbent assay (ELISA) upon ICU admission. Clinical parameters and standard laboratory test data were also collected. All patients received follow-up for at least 28 days. Results: Patients with sepsis presented with significantly decreased serum levels of parkin, Mfn2, and PGC-1α, but an increased serum Fis1 level and Fis1/parkin, Fis1/Mfn2, and Fis1/PGC-1α ratios at ICU admission. Relative to patients with simple infections, the ratios were remarkably elevated in septic patients—particularly septic shock patients. The area under the receiver operating characteristic (ROC) curve of the Fis1/parkin ratio was greater than that of Fis1, parkin, Mfn2, and PGC-1α levels as well as that of the Fis1/Mfn2 and Fis1/PGC-1α ratios for prediction of 28-day mortality due to sepsis. All of the ratios were significantly higher in nonsurvivors than survivors at the 28-day follow-up examination. Fis1/parkin ratio was found to be an independent predictor of 28-day mortality in patients with sepsis. Conclusions: The Fis1/parkin ratio is valuable for risk stratification in patients with sepsis and is associated with poor clinical outcomes for sepsis in the ICU.